Strategi Pengembangan UMKM Berbasis Ikan di Kampung Patin Kecamatan Belitang Kabupaten OKU Timur - fifian permata sari; Harwanto .; Yetty Oktarina (Journal of Integrated Agribusiness, 2024)
Patin Village has great potential to continue to be developed as a center for processing catfish and developing fish-based MSMEs in East OKU Regency. Patin fish is a fishery resource that is widely available in East OKU Regency and is currently a source of income for the East OKU community apart from rice and rubber farming. This research aims to analyze strategies that can be formulated and implemented in fish-based MSMEs in Patin Village, Belitang District, East OKU Regency. The research was carried out in Belitang District, East OKU Regency at the catfish processing center (Kampung Patin) in September 2023. The research method used was the survey method and the sampling method used the purposive sampling method, where Poklahsar Barokah MSMEs in Sukosari Village and Poklahsar Sari Patin Village Triyoso as a center for processing catfish in Belitang District, East OKU Regency was chosen as a sample. The data analysis used in this research is SWOT analysis. The results of the research show that business development strategies that can be developed in East OKU Regency are increasing promotions by using existing social media to introduce products, maintaining consumer loyalty by providing maximum service, collaborating with potential distributor agents to increase market share, building or renting place production in a more strategic location and maintain the intensity of group assistants in supervising the group to increase knowledge about strategic management systems and product marketing.